NEED ANALYSIS OF AUTHENTIC MATERIALS ON ENGLISH LANGUAGE TEACHING (A Study at the Second Grade of MA. Daarul Ulum Cihara - Lebak) - Yayu Heryatun; Siti Sulhah; Rina Fitriana (Sean Institute, 2023)
This study was conducted with the aim to analyze the students’ need of authentic materials used in English teaching and learning activities at MA. Daarul Ulum Panyaungan, a school located at Cihara district, Lebak Regency. The participants in this research are the second grade students and the teacher consist of totally 25 students and 1 teacher. The data in this qualitative study gathered by using observation, interview, and literature review. The findings show that authentic materials are more various to choose and very suitable to be used in English listening and speaking skills learning.